Comparison of the dimensional accuracy of two polyvinyl siloxane putty-wash techniques and digital impressions for single implants adjacent to tooth crown preparations - Hamidreza Rajati Haghi; Hossein Dashti; Saeid Sabzevari; Amineh Khoshbakhti; Alireza Dankoub (Journal of Dental Materials and Techniques)
Objective: This study compared the dimensional accuracy of two polyvinyl siloxane putty-wash impression techniques with the digital impression method for single implants adjacent to tooth crown preparations.Methods: Impressions were taken from a dental arch containing a full-metal preparation on the first molar adjacent to a Straumann tissue-level implant at the second premolar site. A laboratory scanner generated a standard tessellation language (STL) file as the reference for comparisons. Three methods were tested, each performed 10 times: (1) one-step putty-wash technique, (2) two-step putty-wash technique, and (3) digital impressions. Dimensional accuracy was assessed by measuring overall die dimensions, die height, die width, and the tooth-implant distance, using Geomagic Wrap software. Statistical analyses included one-way ANOVA and the Kruskal-Wallis test, with significance at P < 0.05.Results: No significant differences were found among the methods for the die height (P = 0.130), die width (P = 0.180), and tooth-implant distance (P = 0.486). However, the digital impression method showed significantly greater overall dimensional accuracy than the one-step putty-wash technique (P = 0.004). The two-step putty-wash method showed no significant difference with the one-step method or digital impressions concerning the overall die accuracy (P > 0.05).Conclusions: Digital impressions demonstrated significantly higher overall dimensional accuracy than the one-step putty-wash technique. Die height, die width, and tooth-implant distance were comparable across methods. Digital impressions are recommended for optimal accuracy when taking impressions from single implants adjacent to tooth crown preparations. The two-step putty-wash method offers a reliable alternative when digital tools are unavailable.